Harvesting split thickness costal cartilage graft - Sunil Gaba; Richa Gupta; Bharat Mishra; Daisy Sahni (Indian Journal of Plastic Surgery, 2017)
Aim: There are few complications associated with harvesting of full thickness coastal cartilage grafts i.e., pneumothorax (0.9%), contour deformities and prolonged post-operative pain. To address these issues, authors devised special scalpel to harvest split-thickness costal cartilage grafts. Materials and Methods: Standard inframammary incision was used for harvesting rib. Incision was made directly over the desired rib. Specially designed scalpel was used to cut through the rib cartilage to the half of the thickness. The study was conducted in two parts – cadaveric and clinical. Results: There was significantly less pain and no pneumothorax in the patients in whom the split thickness graft was harvested. Wounds healed without any complication. Discussion: Thus, newly devised angulated scalpel used in the current study, showed the potential to supply the reconstructive surgeon with split thickness rib graft without risk of complications such as pneumothorax or warping contour deformities and post-operative pain.